Field evaluation of novel insecticides against brown planthopper (Nilaparvata lugens) and white backed planthopper (Sogatella furcifera) in rice - DHAKA, S S; RAI, MONIKA; RAI, M; YADAV, A (The Indian Journal of Agricultural Sciences, 2020)
A field experiment was conducted to evaluate the bioefficacy of novel insecticides against brown planthopper [Nilaparvatha lugens (Stal)] (BPH) and white backed planthopper [Sogatella furcifera (Hoverth)] (WBPH) on rice. The results revealed that field application of triflumezopyrim 10 SC @ 235 ml per ha was found superior and registered 1.88 and 1.26 hoppers per hill against BPH and WBPH followed bypymetrozine 50 WG @ 300g per ha with 2.12 and 1.26 hoppers of BPH and WBPH per hill, respectively. The response of these insecticides was also observed on the yield attributes, with highest grain yield of 55.58 q/ha in triflumezopyrim 10 SC @ 235 ml per ha followed by pymetrozine 50 WG @ 300 g per ha (53.79 q/ ha).